GIS TOURISM WEB BASED OF KAMPUNG SEBERANG RAMAI, PERLIS - Mohd Khairy Kamarudin; Fazly Amri Mohd; Abdul Hapes Mohamed; Ashnita Rahim; Muhammad Safwan Najmi Shaari; Mohd Adhar Abd Samad (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Tourism is an industry with significant economic impact as it contributes to the development of other economic sectors through a multiplier effect. The location of Kampung Seberang Ramai, which is relatively unknown to the public, makes it difficult to discover this area with paper maps. In addition, this area has a good potential to become a tourist attraction in Perlis. Currently, the area is being upgraded by MAIP under the Diraja Program Transformasi Kampung Seberang Ramai project to make it more attractive. The technology of GIS has many potential applications in tourism management and planning. Some of the most important aspects of GIS that could support tourism planning are managing spatial data and providing important value-added information. The objective of this study is to develop a web-based system for Kampung Seberang Ramai, Perlis. This web-based system will allow public users to access and visualize all information about Kampung Seberang Ramai, Perlis. Web-based design and development using SDLC method with waterfall model, digitization process, attribute table creation and software for this research. The software used is ArcGIS, Google Earth Pro, ArcGIS Online, and Wix Web Editor. The method of this study was used to collect the tourism information and present the tourism web-based content for tourists and analyze the user satisfaction in developing web-based content in four phases: Planning, data collection, web-based design and development, and testing phases. The result of this study is the creation of a web-based GIS of Kampung Seberang Ramai that provides history information and supports tourism development in Perlis Land. The benefits of this study will encourage Kampung Seberang Ramai to become an attractive place in the tourism sector and provide benefits to local villages in the form of profit in the socio-economic sector. Kampung Seberang Ramai should become an attractive place in the tourism sector and provide benefits to the local villages in the form of profit in the socio-economic sector.